‘Tea for two generations’ An Intergenerational psychosocial intervention for people with dementia living in care homes - CAROLE BUTLER (2022)
Intergenerational practice has been found to enhance the wellbeing of people living with dementia, and raise awareness of dementia amongst younger generations in several countries globally. The need for intergenerational interventions is recognised in Welsh policy, however, there is currently a limited evidence base for their potential. The aim of this study was to develop, pilot and evaluate an intergenerational intervention, linking university students with care home residents living with dementia. The intervention aimed to enhance the wellbeing of people living with dementia, who may be at risk of social isolation, and raise awareness of dementia among university students, who may form part of the social care workforce in the future. The intervention involved shared activities based on preparing and sharing food, a meaningful activity that is sometimes lacking in care homes in Wales. The intervention was designed to provide relationship, collaboration, comfort, and equality to participants, which form the basis of person-centred care and contact theory. A pragmatic mixed methods research design was adopted, underpinned by the principles of an experimental framework. Data was gathered from participants and care home staff using Dementia Care Mapping, activity feedback sheets, questionnaires and focus groups. In sum, the thesis found that the intervention generally enhanced the mood and engagement of residents living with dementia, and the attitude of students towards dementia. The study provides additional nuanced insights that similar studies have not provided. The findings of this thesis highlighted a need for attachment to people outside of the environment in which they live, amongst plwd in the care home context. IG Interventions delivered in care homes provide the potential to meet this need. Feedback from care staff indicated that the intervention was suitable for a care home environment, and that observing plwd completing the activities prompted them to consider additional opportunities for residents to become engaged in preparing their own food. This study indicated that preparing and sharing food provides a meaningful basis for IG interventions, and that the benefits of IG interventions reported in other countries can be realised in Wales.